PENGARUH MODAL INTELEKTUAL TERHADAP KINERJA KEUANGAN PERBANKAN UMUM SYARIAH BERDASARKAN ISLAMICITY PERFORMANCE INDEX - Nazra, Mulqi; Suazhari, Suazhari (Accounting Departement Economics and Business Faculty Syiah Kuala University, 2019)
The purpose of this reaserch is to examine the influence of intellectual capital toward financial performance based on islamicity performance index of Islamic banks in Indonesia during 2015-2017. The samples of this study are twelve Islamic commercial banks that were initially selected by using purposive sampling method. Islamicity performance index is used as a measurement of financial performance of Islamic banks which are consist of profit sharing ratio and zakat performance ratio. The analysis technique performed in this study is partial least squares (PLS). The results of this reaserch show that Intellectual capital has negative influence to financial performance.